DETERMINATION OF INFLUENCE OF GEOMETRIC PARAMETERS OF PIEZOCERAMIC PLATE ON AMPLITUDE CHARACTERISTICS OF LINEAR PIEZOMOTOR - V. Ya. Halchenko (Електротехніка і електромеханіка, 2019)
Purpose. The purpose of the paper is to determine the influence of the geometric parameters of the stator of a linear piezoceramic motor in the form of a piezoceramic plate on the characteristics of its amplitude oscillations. Methodology. For the research, mathematical modeling in the COMSOL Multiphysics software package was used, taking into account the interrelation of electrostatic and mechanical phenomena. Results. By numerical simulation of the process of operating of a linear piezoceramic motor, a rational ratio of the width to the length of the piezoceramic plate is determined. Originality. The rational value of the thickness h of the piezoceramic plate of the motor is also established. Approximate dependencies are proposed for determining the parameters of the relationship between the geometric dimensions of the piezoceramic plate of a linear piezomotor, which makes it possible to predict its characteristics. The adequacy of calculation models is confirmed by experimental studies. Practical value. The results obtained can be used in the design of piezoceramic motors.